Should the Outsiders be Left Out? Director Stock Options, Expectations and Earnings Management - Boumosleh, Anwar (2012)
We examine the potential confounding effects that awarding outside directors stock options may have on the quality of financial disclosure. By aligning their interests with those of shareholders, directors should be more inclined to monitor and disclose relevant information to investors. Alternatively, stock options increase directors’ compensation sensitivity to firm performance and thus may motivate collusion with management to misreport for short-term financial gain. Our results support the argument that awarding outside directors with options promotes the dissemination of better information to the analyst community. This is reflected in initial forecast errors that are smaller, contain less variance, and have a greater probability of being accurately revised to meet actual earnings in a timely manner, regardless of whether the initial forecasts are positively or negatively biased. A comparison of director and CEO stock options reveals that CEO options only increase the likelihood of lowering overly optimistic expectations; we find no evidence consistent with CEO options increasing the likelihood of walking up pessimistic expectations. Thus, while performance pay to CEOs promotes the practice of maintaining and meeting low expectations, options to outsiders promotes disclosure regardless of the direction of the bias. We find no evidence to suggest director options increase the likelihood of earnings management. Overall, our results indicate that director stock options indeed provide directors with an incentive to promote shareholder interests, but unlike CEO stock options, do not add significant disclosure related agency costs.